Dinamika Makanan Tradisional Tapa Kolo - Serafina Rafaela Ratrosnin; Aliffiati Aliffiati; Anak Agung Ayu Murniasih (Department of Anthropology Udayana University, 2019)
Tapa kolo is interpreted as bamboo rice that is burned. Rice-based Tapa Kolo. Traditional Tapa kolo meals are usually served at sacred ceremonies. Before the grilled first was prayed for by the customs. At the time of traditional ceremony, among bamboo rice burned there